Safety and Effectiveness of Lower Alteplase Dose Driven by Impending Clinical Deterioration Factors in very Elderly Submassive Pulmonary Embolism Patients. Case Series - Quintanilla, Juan; Reyes-Chavez, Maria Fernanda; Jerjes-Sanchez, Carlos; Galindo-Garza, Melissa; Ponce-Barahona, Aldo F; Alegria-Saldivar, Vanessa; Ibarra, Arturo Adrian Martínez; Osorio-Salazar, Armando; Casanova, Jose Alfredo Salinas-; Estrada-Mendizabal, Ricardo J; et al. (Archives of Clinical and Medical Case Reports, 2022)
Although thrombolysis improves the outcome and mortality in submassive (SM) and massive PE, its role is controversial because of the high rate of intracranial hemorrhage. In addition, safety and efficacy are unclear since randomized controlled studies have excluded very elderly patients because of frailty, multiple comorbidities, and a higher risk of bleeding. Therefore, the best thrombolytic regimen is unknown. Furthermore, it is unclear whether the decision-making for thrombolysis is performed according to the guidelines or based on clinical risk factors associated with poor outcomes. We report three very elderly SMPE associated with several impending clinical deterioration factors (ICDF) (in-transit thrombus, saddle thrombus, etc.). Therefore, we decided on 25 mg alteplase in one- or two-hour continuous infusion based on ICDF rather than clinical instability and systolic hypotension. In addition, we initiate DOACs around 48 hours after stopping unfractionated heparin (UFH). As a result, all patients improve right ventricular performance without bleeding complications. Our results suggest that the lower alteplase dose in one- or two-hour continuous infusion, followed by weight-adjusted UFH, was effective and safe, involving a complicated scenario as an intransit thrombus. Also, DOACs standard doses driven by the patient´s characteristics were unrelated to bleeding complications avoiding recurrence in very elderly SMPE.